Skill Sets for Microgrids Sustainability - The Case of East Africa - Bogere, Paul; Bode, Henrik; Temmen, Katrin (2023 IEEE AFRICON)

Should I Really do That? Using Quantile Regression to Examine the Impact of Sanctions on Information Security Policy Compliance Behavior - Hengstler, S.; Kuehnel, S.; Masuch, K.; Nastjuk, I.; Trang, Simon Thanh-Nam (Computers & Security)

A Topic Model for the Data Web - Röder, Michael; Kuchelev, Denis; Ngonga Ngomo, Axel-Cyrille (Knowledge Graphs and Semantic Web)
Keywords: sail dice roeder kuchelev ngonga

Explainable Integration of Knowledge Graphs Using Large Language Models - Ahmed, Abdullah Fathi Ahmed; Firmansyah, Asep Fajar; Sherif, Mohamed; Moussallem, Diego; Ngonga Ngomo, Axel-Cyrille (Natural Language Processing and Information Systems)
Linked knowledge graphs build the backbone of many data-driven applications such as search engines, conversational agents and e-commerce solutions. Declarative link discovery frameworks use complex link specifications to express the conditions under which a link between two resources can be deemed to exist. However, understanding such complex link specifications is a challenging task for non-expert users of link discovery frameworks. In this paper, we address this drawback by devising NMV-LS, a language model-based verbalization approach for translating complex link specifications into natural language. NMV-LS relies on the results of rule-based link specification verbalization to apply continuous training on T5, a large language model based on the Transformerarchitecture. We evaluated NMV-LS on English and German datasets using well-known machine translation metrics such as BLUE, METEOR, ChrF++ and TER. Our results suggest that our approach achieves a verbalization performance close to that of humans and outperforms state of the art approaches. Our source code and datasets are publicly available at https://github.com/dice-group/NMV-LS.

Unsupervised Relation Extraction with Sentence level Distributional Semantics - Manzoor, Ali; Saleem, Muhammad; Ngonga Ngomo, Axel-Cyrille (2023 IEEE 17th International Conference on Semantic Computing (ICSC))

Automating the Discovery of Linking Candidates - Röder, Michael
Keywords: dice roeder

Neural Class Expression Synthesis (Extended Abstract) - KOUAGOU, N'Dah Jean; Heindorf, Stefan; Demir, Caglar; Ngonga Ngomo, Axel-Cyrille (NeSy 2023, 17th International Workshop on Neural-Symbolic Learning and Reasoning, Certosa di Pontignano, Siena, Italy)
Keywords: 318 SFB-TRR demir dice enexa heindorf knowgraphs kouagou ngonga sail

Using Pre-trained Language Models for Abstractive DBPEDIA Summarization: A Comparative Study - Zahera, Hamada Mohamed Abdelsamee; Vitiugin, Fedor; Sherif, Mohamed; Castillo, Carlos; Ngonga Ngomo, Axel-Cyrille (SEMANTiCS)
Keywords: dice kiam ngonga porque sherif zahera

LauNuts: A Knowledge Graph to identify and compare geographic regions in the European Union - Wilke, Adrian; Ngonga Ngomo, Axel-Cyrille (The Semantic Web (ESWC 2023))
Keywords: dice eml4u ngonga opal wilke

Native Execution of GraphQL Queries over RDF Graphs Using Multi-way Joins - Karalis, Nikolaos; Bigerl, Alexander; Ngonga Ngomo, Axel-Cyrille (SEMANTiCS)
Keywords: bigerl dice enexa karalis knowgraphs ngonga sail

Parameterized Complexity of Logic-based Argumentation in Schaefer’s Framework - Mahmood, Yasir; Meier, Arne; Schmidt, Johannes (ACM Transactions on Computational Logic)
Argumentation is a well-established formalism dealing with conflicting information by generating and comparing arguments. It has been playing a major role in AI for decades. In logic-based argumentation, we explore the internal structure of an argument. Informally, a set of formulas is the support for a given claim if it is consistent, subset-minimal, and implies the claim. In such a case, the pair of the support and the claim together is called an argument. In this article, we study the propositional variants of the following three computational tasks studied in argumentation: ARG (exists a support for a given claim with respect to a given set of formulas), ARG-Check (is a given set a support for a given claim), and ARG-Rel (similarly as ARG plus requiring an additionally given formula to be contained in the support). ARG-Check is complete for the complexity class DP, and the other two problems are known to be complete for the second level of the polynomial hierarchy (Creignou et al. 2014 and Parson et al., 2003) and, accordingly, are highly intractable. Analyzing the reason for this intractability, we perform a two-dimensional classification: First, we consider all possible propositional fragments of the problem within Schaefer’s framework (STOC 1978) and then study different parameterizations for each of the fragments. We identify a list of reasonable structural parameters (size of the claim, support, knowledge base) that are connected to the aforementioned decision problems. Eventually, we thoroughly draw a fine border of parameterized intractability for each of the problems showing where the problems are fixed-parameter tractable and when this exactly stops. Surprisingly, several cases are of very high intractability (para-NP and beyond).

Quantitative Reasoning and Structural Complexity for Claim-Centric Argumentation - Fichte, Johannes K.; Hecher, Markus; Mahmood, Yasir; Meier, Arne (Proceedings of the Thirty-Second International Joint Conference on Artificial Intelligence)
Argumentation is a well-established formalism for nonmonotonic reasoning and a vibrant area of research in AI. Claim-augmented argumentation frameworks (CAFs) have been introduced to deploy a conclusion-oriented perspective. CAFs expand argumentation frameworks by an additional step which involves retaining claims for an accepted set of arguments. We introduce a novel concept of a justification status for claims, a quantitative measure of extensions supporting a particular claim. The well-studied problems of credulous and skeptical reasoning can then be seen as simply the two endpoints of the spectrum when considered as a justification level of a claim. Furthermore, we explore the parameterized complexity of various reasoning problems for CAFs, including the quantitative reasoning for claim assertions. We begin by presenting a suitable graph representation that includes arguments and their associated claims. Our analysis includes the parameter treewidth, and we present decomposition-guided reductions between reasoning problems in CAF and the validity problem for QBF.

Parameterized Complexity of Propositional Inclusion and Independence Logic - Mahmood, Yasir; Virtema, Jonni (Logic, Language, Information, and Computation)

Logics with probabilistic team semantics and the Boolean negation - Hannula, Miika; Hirvonen, Minna; Kontinen, Juha; Mahmood, Yasir; Meier, Arne; Virtema, Jonni (18th European Conference on Logics in Artificial Intelligence, JELIA 2023, Proceedings)
Keywords: dice enexa mahmood

Configuration and Evaluation - Hanselle, Jonas Manuel; Hüllermeier, Eyke; Mohr, Felix; Ngonga Ngomo, Axel-Cyrille; Sherif, Mohamed; Tornede, Alexander; Wever, Marcel Dominik (On-The-Fly Computing – Individualized IT-services in dynamic markets)
Keywords: dice ngonga sfb901 sherif

Lingua Franca - Entity-Aware Machine Translation Approach for Question Answering over Knowledge Graphs - Srivastava, Nikit; Perevalov, Aleksandr; Kuchelev, Denis; Moussallem, Diego; Ngonga Ngomo, Axel-Cyrille; Both, Andreas (Proceedings of the 12th Knowledge Capture Conference 2023, K-CAP 2023, Pensacola, FL, USA, December 5-7, 2023)
Keywords: dice kuchelev moussallem ngonga srivastava

Learning Permutation-Invariant Embeddings for Description Logic Concepts - Demir, Caglar; Ngonga Ngomo, Axel-Cyrille (Advances in Intelligent Data Analysis XXI: 21st International Symposium on Intelligent Data Analysis, IDA 2023, Louvain-la-Neuve, Belgium, April 12–14, 2023, Proceedings)
Keywords: 318 SFB-TRR demir dice enexa ngonga sail

COBALT: A Content-Based Similarity Approach for Link Discovery over Geospatial Knowledge Graphs - Becker, Alexander; Ahmed, Abdullah Fathi Ahmed; Sherif, Mohamed; Ngonga Ngomo, Axel-Cyrille (SEMANTiCS)
Keywords: ahmed becker dice ngonga sail sherif

Method Engineering – a Systematic Literature Review on Scopus Base - Wilke, Daria; Grewe, Carolin; Thavathilakarjah, Dhusjanth; Anacker, Harald; Dumitrescu, Roman

Method to support the selection of localization technologies for Industry 4.0 - Seidenberg, Tobias; Ayoub, Joe; Figge, Mike; Anacker, Harald; Dumitrescu, Roman